A mixed methods approach towards understanding key disease characteristics associated with the progression from RRMS to SPMS: Physicians’ and patients’ views - Ziemssen, Tjalf; Tolley, Chloe; Bennett, Bryan; Kilgariff, Sarah; Jones, Eddie; Pike, James; Tomic, Davorka; Piani-Meier, Daniela; Lahoz, Raquel (Multiple sclerosis and related disorders, 2020)
•The mechanisms of transition from RRMS to SPMS are poorly understood.•This was the first stage of development of a novel tool to assess the signs of progression.•Both qualitative and quantitative methods were used to determine tool content.•Physicians confirmed the usefulness of this tool in clinical practice. The transition from relapsing-remitting multiple sclerosis (RRMS) to secondary progressive multiple sclerosis (SPMS) evolves over time and it can be challenging for physicians to identify progression early. Typically, SPMS is diagnosed retrospectively with a significant delay, based on a history of gradual worsening, independent of relapses, following an initial relapsing-remitting disease course. As such, SPMS is often associated with a considerable period of diagnostic uncertainty. This study aimed to explore and characterize key symptoms and impacts associated with transitioning from RRMS to SPMS and inform the content for a tool to support evaluation of early subtle signs suggestive of progressive disease. The qualitative study involved 60-min, face-to-face, concept elicitation (CE) interviews with 32 patients with MS (US = 16 and Germany = 16); and 30-min, telephone, CE interviews with 16 neurologists (US = 8 and Germany = 8). Multivariate analysis on data from a real-world observational study of 3294 MS patients assessed the differences between early-RRMS and early-SPMS, and identified factors that were significant drivers of this difference. These studies informed selection of the key variables to be included in a pilot tool. Sixteen physicians used the pilot tool, presented as a paper questionnaire, with a sample of patients whom they suspected were progressing to SPMS (n ≥ 5). Following this, the physicians participated in a 30-min cognitive debriefing (CD) interview to evaluate the relevance and usefulness of the tool. Qualitative analysis of all anonymized, verbatim transcripts was performed using thematic analysis. Patients and physicians reported signs that indicated progression to SPMS including gradual worsening of symptoms, lack of clear recovery, increased severity and presence of new symptoms. No specific symptoms definitively indicated progression to SPMS, however a number of potential symptoms associated with progression were identified by SPMS patients and physicians, including worsening ambulation, cognition, balance, muscle weakness, visual symptoms, bladder symptoms and fatigue. Quality of life domains reported to be more severely impacted in SPMS than MS in general included: physical activity, work, daily activities, emotional and social functioning. Multivariate analysis of the observational study data identified several variables strongly associated with progression to SPMS including, requirement of assistance in daily living, presence of motor symptoms, presence of ataxia/coordination symptoms, and unemployment. Physicians reported that items included in the tool were easy to understand and relevant. Physicians also reported that there is an unmet need for a tool to help identify signs of SPMS progression and so the tool would be useful in clinical practice. This was the first stage of development of a novel, validated, physician-completed tool to support physician–patient interactions in evaluating signs indicative of disease progression to SPMS. Qualitative and quantitative methods (involving physician and patients) were used to determine tool content. The usefulness and unmet need for such a tool in clinical practice was confirmed via CD interviews with physicians. Further work is now warranted to develop a scoring algorithm and validate the tool so that it can be reliably implemented in clinical practice.